(untitled) (Bangladesh Rice Journal, 2025)
The local climate greatly influences the development of a crop including factors such as temperature, rainfall, light intensity, radiation, and sunshine duration. Thermal units are closely linked to various physiological processes at each stage of crop development and can serve as a valuable tool for assessing thermal response. To explore this, a study was conducted to evaluate the grain yield and thermal unit requirements for the phenological development of four rice varieties under different seeding dates. Seeding took place from 15 November to 30 December, at 15-day intervals. The findings revealed that the seeding date had a significant impact on the thermal unit requirements for crop phenology and yield. Earlier seeding resulted in a higher accumulation of degree days compared to later seeding, as the crops required the most thermal input to complete panicle initiation. Seeding date notably affected the accumulated Growing Degree Days (GDD) from sowing to panicle initiation, heading, full flowering, and maturity. The GDD requirements for physiological maturity were the highest for the November 15 seeding, with the required GDD decreasing as seeding was delayed. The accumulated GDD for physiological maturity across the four varieties under different seeding dates ranged as follows: BRRI dhan96 (1972 to 2112 °C day), BRRI dhan97 (2116 to 2267 °C day), BRRI dhan99 (2097 to 2267 °C day), and BRRI dhan100 (2031 to 2183 °C day). Along with GDD, Heat Use Efficiency (HUE), Helio Thermal Units (HTU), and Photothermal Units (PTU) were identified as useful metrics for estimating crop growth and development based on temperature and solar radiation. In terms of yield, BRRI dhan96 achieved the highest yield when seeded on 30 November, outperforming the other three varieties (BRRI dhan97, BRRI dhan99, and BRRI dhan100). Therefore, the study concludes that seeding between 15 and 30 November optimizes heat use efficiency, leading to better physiological responses and higher yields. Bangladesh Rice J. 27(2): 39-50, 2023